Spatiotemporal variation of bacterial communities in three cascade reservoirs in a southern city of China - Guangqiang Cai (IWA Publishing, 2021)
Reservoirs are important water sources of urban drinking water supply. Bacteria play an important role in the removal of organics in reservoirs, but some of them can pose a health risk to consumers. Knowledge of bacterial community composition in drinking water sources can favour the drinking water security safeguards. This study investigated the monthly composition and diversity of bacterial communities in three cascade reservoirs using high-throughput Illumina HiSeq sequencing over one hydrological year. The diversity and structure of the bacterial community showed distinct spatiotemporal variation. Mycobacterium, Acinetobacter, Sphingomonas, Sphingobacterium and Pseudomonas were the genera resistant to chlorine. In addition, Acinetobacter, Arcobacter, Mycobacterium, Pseudomonas and Staphylococcus were the main potential pathogenic genera. The bacterial community diversity and the average relative abundance of potential pathogenic genera detected in the wet season were higher than those in the dry season. Water temperature was found to be the main factor for the temporal variation. The spatial variation of bacterial community diversity and the average relative abundance of potential pathogenic genera were related to water current and the degree of water pollution, respectively. The results of this study can conduce the beneficial management of drinking water treatment processes. HIGHLIGHTS Bacterial communities in three cascade reservoirs showed spatiotemporal variation.; Bacterial diversity and potential pathogenic genera abundance were higher in the wet season.; Water temperature was the major factor leading to the temporal variation.; The spatial variation was related to water current and the degree of water pollution.;